{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

57319-0136147054_06

# 57319-0136147054_06 - Section 6.1 n 6.1.1 With a = 0 and b...

This preview shows pages 1–4. Sign up to view the full content.

Section 6.1 6.1.1: With a = 0 and b = 1, lim n →∞ n i =1 2 x i x = 1 0 2 x dx = x 2 1 0 = 1. 6.1.2: With a = 1 and b = 2, lim n →∞ n i =1 x ( x i ) 2 = 2 1 1 x 2 dx = 1 x 2 1 = 1 2 . 6.1.3: With a = 0 and b = 1, lim n →∞ n i =1 (sin πx i ) ∆ x = 1 0 sin πx dx = 1 π cos πx 1 0 = 2 π . 6.1.4: With a = 1 and b = 3, lim n →∞ n i =1 3 ( x i ) 2 1 x = 3 1 (3 x 2 1) dx = x 3 x 3 1 = 24. 6.1.5: With a = 0 and b = 4, lim n →∞ n i =1 x i ( x i ) 2 + 9 ∆ x = 4 0 x x 2 + 9 dx = 1 3 ( x 2 + 9) 3 / 2 4 0 = 125 3 9 = 98 3 . 6.1.6: The limit is 4 2 1 x dx = ln x 4 2 = ln 4 ln 2 = 2 ln 2 ln 2 = ln 2. 6.1.7: The limit is 1 0 e x dx = e x 1 0 = e 0 e 1 = 1 1 e . 6.1.8: The limit is 4 0 2 x + 1 dx = 1 3 (2 x + 1) 3 / 2 4 0 = 9 1 3 = 26 3 . 6.1.9: The limit is 6 0 x x 2 + 9 dx = 1 2 ln( x 2 + 9) 6 0 = 1 2 ln 45 1 2 ln 9 = 1 2 ln 5. 6.1.10: The limit is 1 0 2 x exp( x 2 ) dx = exp( x 2 ) 1 0 = e 0 e 1 = 1 1 e . 6.1.11: With a = 1 and b = 4, lim n →∞ n i =1 2 πx i f ( x i ) ∆ x = 4 1 2 πxf ( x ) dx. Compare this with Eq. (2) in Section 6.3. 6.1.12: With a = 1 and b = 1, lim n →∞ n i =1 [ f ( x i )] 2 x = 1 1 [ f ( x ) ] 2 dx . 6.1.13: With a = 0 and b = 10, lim n →∞ n i =1 1 + [ f ( x i ) ] 2 x = 10 0 1 + [ f ( x ) ] 2 dx . 6.1.14: With a = 2 and b = 3, we have lim n →∞ n i =1 2 πm i 1 + [ f ( m i ) ] 2 x = 3 2 2 πx 1 + [ f ( x ) ] 2 dx. 524

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
6.1.15: M = 100 0 1 5 x dx = 1 10 x 2 100 0 = 1000 0 = 1000 (grams). 6.1.16: M = 25 0 (60 2 x ) dx = 60 x x 2 25 0 = 875 0 = 875 (grams). 6.1.17: M = 10 0 x (10 x ) dx = 5 x 2 1 3 x 3 10 0 = 500 3 0 = 500 3 (grams). 6.1.18: M = 10 0 10 sin πx 10 dx = 100 π cos πx 10 10 0 = 100 π 100 π = 200 π (grams). 6.1.19: The net distance is 10 0 ( 32) dt = 32 t 10 0 = 320 and the total distance is 320. 6.1.20: The net distance is 5 1 (2 t + 10) dt = t 2 + 10 t 5 1 = 75 11 = 64 and because v ( t ) = 2 t + 10 0 for 1 t 5, this is the total distance as well. 6.1.21: The net distance is 10 0 (4 t 25) dt = 2 t 2 25 t 10 0 = 200 250 = 50 . Because v ( t ) = 4 t 25 0 for 0 t 6 . 25 and v ( t ) 0 for 6 . 25 t 10, the total distance is 6 . 25 0 v ( t ) dt + 10 6 . 25 v ( t ) dt = 625 8 + 225 8 = 425 4 = 106 . 25 . 6.1.22: Because v ( t ) 0 for 0 t 5, the net and total distance are both equal to 5 0 | 2 t 5 | dt = 2 . 5 0 (5 2 t ) dt + 5 2 . 5 (2 t 5) dt = 25 4 + 25 4 = 25 2 = 12 . 5 . 6.1.23: The net distance is 3 2 4 t 3 dt = t 4 3 2 = 81 16 = 65 . Because v ( t ) 0 for 2 t 0, the total distance is 0 2 4 t 3 dt + 3 0 4 t 3 dt = 16 + 81 = 97 . 525
6.1.24: The net distance is 1 0 . 1 t 1 t 2 dt = 1 2 t 2 + 1 t 1 0 . 1 = 3 2 2001 200 = 1701 200 = 8 . 505 . Because v ( t ) 0 for 0 . 1 t 1, the total distance is 8 . 505. 6.1.25: Because v ( t ) = sin 2 t 0 for 0 t π/ 2, the net distance and the total distance are both equal to π/ 2 0 sin 2 t dt = 1 2 cos 2 t π/ 2 0 = 1 2 1 2 = 1 . 6.1.26: The net distance is π/ 2 0 cos 2 t dt = 1 2 sin 2 t π/ 2 0 = 0 0 = 0 . Because v ( t ) = cos 2 t 0 for π/ 4 t π/ 2, the total distance is π/ 4 0 cos 2 t dt π/ 2 π/ 4 cos 2 t dt = 1 2 + 1 2 = 1 . 6.1.27: The net distance is 1 1 cos πt dt = 1 π sin πt 1 1 = 0 0 = 0 . Because v ( t ) = cos πt 0 for 1 t 0 . 5 and for 0 . 5 t 1, the total distance is 0 . 5 1 cos πt dt + 0 . 5 0 . 5 cos πt dt 1 0 . 5 cos πt dt = 1 π + 2 π + 1 π = 4 π .

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### What students are saying

• As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

Kiran Temple University Fox School of Business ‘17, Course Hero Intern

• I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

Dana University of Pennsylvania ‘17, Course Hero Intern

• The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

Jill Tulane University ‘16, Course Hero Intern